First-year teachers' dispositions: exhibited and perception of being taught - Kirchner, Shane (Kansas State University, 2011)
The National Council for the Accreditation of Teacher Education (NCATE) standards adopted in 2000 mandated the assessment of teacher dispositions. However, the lack of specificity of the construct has led to an environment where many institutions struggle to develop high-quality disposition assessments. The result is a hodgepodge of constructs and systems; some that work, some that do not. This quantitative study used a modified version of the Teacher Disposition Index (TDI) to identify the extent to which first-year teachers’ self-reported exhibiting the dispositions and whether they perceived they were taught the dispositions by the teacher education programs from which they graduated. Responses to the TDI were compared based on type of college or university from which they graduated, gender and age. The TDI, a 45 item, Likert-type survey, is aligned with the INTASC standards. Data were analyzed using frequency distributions, analysis of variance, and chi square tests. An aggregate review of all 45 dispositions shows 93.6% of responses were positive for “agree” or “strongly agree” that they exhibit the identified dispositions and 88.51% of responses were positive for perceiving they were taught the dispositions. Overall, there was no significant difference identified between any groups (by school type, gender, or age) except for in exhibited dispositions compared by gender (p< .05). When drilling down to specific dispositions, an occasional significant difference was identified. In general, the respondents in this state report they exhibit the identified dispositions at a high rate and they report the teacher education programs are teaching these dispositions. The following recommendations are made based on the results of this study. First, colleges and universities can teach more interpersonal communications skills as part of the required curriculum. More overt instruction of dispositions, especially at smaller institutions, is needed. Teacher education programs could place more emphasis on the development of dispositions of male teacher education candidates. Novice teachers could benefit from more instruction of informal assessment skills and flexibility in instruction.
Keywords: Dispositions; Teacher education; Teacher Education (0530)